(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article analyses the legal treatment of animals used in scientific research in the constitutional perspective of the balance between the needs of man and those of animal welfare. The evolution of “animal dignity” is then reconstructed and the proposals for amending Italian Constitution are analysed. The article focuses on the evolution of the Italian regulation on animal experimentation, paying attention to the influence of public opinion on the development of legislation. Finally, a different perspective is proposed to the balance between research and care of animals, assuming the compatibility of them from the perspective of greater reliability of an experiment respectful of animal welfare.